2002
DOI: 10.1007/s00415-002-0690-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of thrombophilic risk factors in patients with dural arteriovenous fistulas

Abstract: Dural arteriovenous fistulas (DAVFs) are direct artery-to-cerebral venous sinus shunts. Our recent finding of a significantly increased prevalence of factor V (FV) Leiden in patients with DAVFs prompted us to evaluate prothrombinG20210A, MTHFRC677T, beta-fibrinogenG455A, PAI-14G/5G and FXIIIVal34Leu as additional risk factors for thrombophilia in 26 patients with DAVFs and a group of age- and gender-matched controls. There was no significantly increased prevalence of these risk factors in DAVF patients. We con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 15 publications
0
14
1
Order By: Relevance
“…In contrast, a factor V Leiden mutation was found in only 1 patient (4.0%) with cDAVF, which is within the range of the reported incidence of 5% in the Caucasian population (9). Therefore, our data are in contrast to the studies of Kraus et al (23,25), who found an increased prevalence of the factor V Leiden mutation in patients with cDAVF compared with ageand sex-matched controls, whereas the G20210A mutation of the prothrombin gene was not increased (24). This discrepancy is difficult to explain, and it is unlikely that the ethnic background differs between the 2 study populations.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…In contrast, a factor V Leiden mutation was found in only 1 patient (4.0%) with cDAVF, which is within the range of the reported incidence of 5% in the Caucasian population (9). Therefore, our data are in contrast to the studies of Kraus et al (23,25), who found an increased prevalence of the factor V Leiden mutation in patients with cDAVF compared with ageand sex-matched controls, whereas the G20210A mutation of the prothrombin gene was not increased (24). This discrepancy is difficult to explain, and it is unlikely that the ethnic background differs between the 2 study populations.…”
Section: Discussioncontrasting
confidence: 84%
“…Although a few authors consider hypercoagulopathy in the pathogenesis of cDAVF (13,19,20,(23)(24)(25)44), findings in their studies are not uniform. In this study, 35% of patients with cDAVF and sDAVF had thrombophilic risk factors.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Its drainage route gradually occludes from the inferior petrosal sinus and superior ophthalmic vein 11 , and occasionally causes a paradoxical worsening of visual acuity and chemosis with ocular hypertension following occlusion of the anterior drainage route. During this progression, the thrombophilic abnormalities characteristic of DAVF are also reported [18][19][20][21][22] .…”
Section: Hypothesismentioning
confidence: 74%
“…1,4,[10][11][12]15 The causal role of venous thrombosis is supported by the association of DAVF with hypercoagulable states, such as hyperhomocysteinemia, factor V Leiden, and antithrombin, protein C and S deficiencies. 2,[15][16][17][18][19][20] However, it is important to note that dural sinus thrombosis or occlusion can also be a sequelae of DAVF, likely resulting from associated venous hypertension. Finally, although many cases of DAVF are sporadic with no identifiable cause, some patients will report a history of intracranial surgery, infection, radiation exposure, pregnancy, or trauma.…”
Section: Epidemiology and Pathophysiologymentioning
confidence: 99%